Characteristics of the microstructure, magnetic and antibacterial properties of silver-substituted cobalt ferrite nanoparticles from the sol-gel method - Riyatun Riyatun; Triana Kusumaningsih; Agus Supriyanto; Budi Purnama (Kuwait Journal of Science)
This paper reports the structural characteristics and magnetic properties of silver (Ag+) doped cobalt ferrite nanoparticles AgxCo1-xFe2O4 (x ​= ​0, 0.01, 0.02, 0.03, 0.1) associated with their ability as antibacterial agents. The synthesis of the material was carried out by the sol-gel method. The atomic structure confirmed by the XRD pattern is a single-phase cubic spinel having a characteristic peak (311) at low Ag doping. Meanwhile, at high Ag doping (x ​= ​0.1), another phase was formed which correspond to Ag3O4. Increasing the concentration of Ag ​+ ​causes the crystallite size to increase slightly, from 14 to 21 ​nm. The FTIR spectroscopy showed that M ​− ​O bonds at the tetrahedral and octahedral sites confirmed that the cobalt-based ferrite's spinel phase was preserved. The increased Ag doping changes the constant's force at the tetrahedral site for Ag–CoFe2O4 is higher than for CoFe2O4. And the changes were more evident at the octahedral than at the tetrahedral sites. Ion migration may be more dominant in the octahedral site. The VSM test showed that Ag+doping on CoFe2O4 reduced the coercive field for both low and high doping. The magnetic parameters, i.e., saturation magnetization, remanent magnetization, magnetic anisotropy, and magnetic moment decreased in low Ag doping and increased for high Ag doping. The saturation magnetization of pure CoFe2O4 (x ​= ​0) was 37.55 emu.g−1, but the low-doped Ag–CoFe2O4 was 31 emu.g−1. These changes are attributed to the redistribution of cations at the tetrahedral and octahedral sites due to the replacement of Co2+ ions with Ag+ions. The antibacterial test against S. aureus and E. coli showed that all doping of Ag+concentration had antibacterial properties but was more potent at low-doped Ag–CoFe2O4. The ratio of ZoI in both bacteria reached 14.68%, and mortality at 87%.